2009
DOI: 10.1111/j.1475-1305.2008.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Methods to Estimate Creep Damage in Low‐Alloy Steel Power Station Steam Pipes

Abstract: ABSTRACT:For large complex structures such as power stations, refineries and other processing plants, cost effective operation is essential. With power stations, failures of components without prior warning can have serious consequences for personnel on site and be extremely expensive in terms of both losses in generation revenue and repair costs. The ability to monitor and assess the evolution of damage is critical to maximising plant availability and to minimise the risk of failures that pose a threat to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Laboratory tests have shown that the strain typically accumulated in Cr-Mo-V steel components over a 2-year period of plant operation can be measured with an error of less than 10% [128]. The silicon nitride targets are not affected by the formation of scale on the surface of the component, but they do tend to become dull with time after exposure to high temperatures, so that degradation of image quality is currently an issue [129].…”
Section: Strain Gaugesmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory tests have shown that the strain typically accumulated in Cr-Mo-V steel components over a 2-year period of plant operation can be measured with an error of less than 10% [128]. The silicon nitride targets are not affected by the formation of scale on the surface of the component, but they do tend to become dull with time after exposure to high temperatures, so that degradation of image quality is currently an issue [129].…”
Section: Strain Gaugesmentioning
confidence: 99%
“…Accurate strain measurements can be obtained in shortterm laboratory tests [132], whereas work is in progress to ensure that the inevitable degradation of the speckle pattern due to high temperatures and harsh in situ environmental conditions yields images of sufficiently high quality between maintenance intervals, at which time the strain map could be stored and the pattern re-applied [129,133]. It is postulated that this technique could be successfully employed for the early detection and assessment of creep damage across welds because highly localised increases of the strain rate in the HAZ would be easily recorded [129].…”
Section: Digital Image Correlationmentioning
confidence: 99%
“…Following the review work of Maharaj et al and Sposito et al , there have been some recent developments with respect to methods used to measure creep deformation. These include using magnetic field properties that measure Barkhausen noise or magnetic hysteresis, eddy currents that are disrupted by inhomogeneities and replicas where computer‐based image analysis has shown some promise .…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the future trends of power plant operation, these fluctuations will become more pronounced as operators attempt to generate in a highly strategic manner, maximising generation effectiveness [4]. Variations in loading or temperature present serious complications when analysing such components due to the cyclic hardening and/or softening behaviour of materials if the material works within the plastic range.…”
Section: Introductionmentioning
confidence: 99%